Emerging Business Paradigms in the Digital and Agribusiness Sectors: Integrative Insights from Consumer Behavior, Technological Innovation, and Sustainable Development - Fuzail, Muhammad; Shareef, Shahdat (PROCURATIO: Jurnal Manajemen & Bisnis, 2025)
Purpose – This study aims to explore and synthesize emerging business paradigms in the digital and agribusiness sectors by examining how consumer behavior, technological innovation, and sustainability converge to shape strategic business practices. Grounded in both theoretical and practical contexts, the research addresses the need for more integrated, adaptive approaches that respond to the rapidly evolving market and societal demands in digital economies and agri-based systems. Design/method/approach – The research adopts a qualitative multiple-case study approach, combining a systematic review of recent literature with semi-structured interviews involving practitioners from digital and agribusiness sectors in Southeast Asia. Data were analyzed thematically using triangulation to identify cross-cutting patterns, strategic insights, and emergent trends that highlight integrative business dynamics. Findings – The study finds a paradigmatic shift toward value co-creation with consumers, the strategic use of immersive technologies for emotional branding, the growing importance of localized innovation strategies, and the systemic integration of sustainability practices. Interviewees emphasize agility, empathy, and collaboration as key competencies in navigating the shift from transactional to relational value models. These insights reinforce the need for ecosystem-based approaches and socially embedded technological adoption. Implications – The findings offer valuable contributions to both theory and practice by illustrating how socio-technical systems thinking and glocalization strategies can guide business transformation. For practitioners, the research underscores the importance of aligning innovation with local context, embedding sustainability into the core of strategy, and fostering consumer-driven engagement in both digital and agribusiness sectors. Novelty/Originality – This study contributes a novel cross-sectoral perspective by bridging digital and agribusiness insights through an integrative analytical lens. It fills a critical gap in literature by illustrating how business paradigms are evolving holistically, particularly in underexplored emerging markets, with practical implications for sustainable competitiveness.